2015
DOI: 10.1021/acs.jmedchem.5b00150
|View full text |Cite
|
Sign up to set email alerts
|

DARC: Mapping Surface Topography by Ray-Casting for Effective Virtual Screening at Protein Interaction Sites

Abstract: Protein-protein interactions represent an exciting and challenging target class for therapeutic intervention using small molecules. Protein interaction sites are often devoid of the deep surface pockets presented by “traditional” drug targets, and crystal structures reveal that inhibitors typically engage these sites using very shallow binding modes. As a consequence, modern virtual screening tools developed to identify inhibitors of traditional drug targets do not perform as well when they are instead deploye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 116 publications
(286 reference statements)
0
25
0
Order By: Relevance
“…S2). We note that this methodology also identifies those interactions that are particularly strong (K D value of less than 10 Ϫ7 M) (29). In this way, we found that many of the interactions between the proteins and STPKs were indeed strong, including PknB -EchA7, PknD -FtsX, PknG -PhoH2, and PknH -AccD6.…”
Section: Global Identification Of Kpis Using Mtb Proteome Microarrays-mentioning
confidence: 60%
“…S2). We note that this methodology also identifies those interactions that are particularly strong (K D value of less than 10 Ϫ7 M) (29). In this way, we found that many of the interactions between the proteins and STPKs were indeed strong, including PknB -EchA7, PknD -FtsX, PknG -PhoH2, and PknH -AccD6.…”
Section: Global Identification Of Kpis Using Mtb Proteome Microarrays-mentioning
confidence: 60%
“…DARC (Docking Approach using Ray-Casting) [61] is specifically designed to handle the shallow, flat pockets, which is typically observed in PPI sites. DARC works by comparing the topology of a protein surface pocket to the topology of a bound ligand at the binding site.…”
Section: Computational Methods 1: Screening Full Ligandsmentioning
confidence: 99%
“…Although there are some examples where CADD has been applied to SMPPII discovery [21–23], PPIs remain difficult targets since PPIs and their binding ligands have different characteristics from traditional targets. [24, 25]. To understand the current status of CADD methods for PPI targets, here we review computational tools for discovering SMPPIIs, which try to overcome the hurdles that arise from the different nature of PPIs and compounds that interact with PPIs.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, these pockets can also be used for Rosetta's Docking Approach using Ray Casting (DARC 31 ) method. DARC uses ray-casting to rapidly position a ligand in the protein surface pocket 31 ; by iterating over many candidates, DARC provides a means for very rapid virtual screening. DARC has also been adapted for GPUs 32 , and the newer implementation 33 includes features that provide improved performance in virtual screening benchmarks.…”
Section: Elucidating Interfaces Between Proteins and Small Molecule Lmentioning
confidence: 99%